Conflicts of human with the Tibetan brown bear (Ursus arctos pruinosus) in the Sanjiangyuan region, China - Yunchuan Dai; Charlotte E. Hacker; Yuguang Zhang; Ye Li; Jia Li; Yadong Xue; Diqiang Li (Global Ecology and Conservation, 2020)
Human-carnivore conflict (HCC) has become a major concern for both the management of protected areas and local community development worldwide. The occurrence and intervention of HCCs has been originated in duel context of the environment and social economy. In the Sanjiangyuan region of the Qinghai-Tibet Plateau, human-bear conflict (HBC) has emerged as a severe problem. Damages caused by Tibetan brown bears (Ursus arctos pruinosus) seriously threaten the livelihood and safety of local herders, decreasing community tolerance for brown bear conservation. A systematic field survey of HBC occurrences was undertaken in Zhiduo county of the Sanjiangyuan region in summer 2019. We surveyed 312 families via semi-structured interviews to understand the factors that contributed towards the likelihood of bear damage, representative conflict types, seasonal variation in damage occurrence, and mitigation measures deployed. The results showed that incidents of bear damage in the Sanjiangyuan region have elevated as a consequence of changes in the nomadic lifestyle of local herders. It is in part connected with simultaneous recovery of bear numbers following the conservation measures applied. Despite the widespread incidence of HBCs, with almost all respondents (n = 288, 92.31%) reporting occurrences of bear damage, most home damages were not compensated, and programs for such were lacking. Through the survey of the expected compensation types of local respondents, it was concluded that HBCs need to be mediated and resolved by integrated compensation schemes, physical and chemical prevention measures, and community development plans. Particularly, the local government should pay more attention to reducing family dependence on animal husbandry and transforming livelihood strategies into replaceable economic practices unrelated to grazing. These include things like ecological public welfare jobs and brown bear viewing ecotourism.